Allah dalam Perspektif Pendidikan Kristen: Landasan Teologis Pembentukan Moral Anak - Winar Septriani Zebua; Yupiter Laia; Erna Sari Halawa; Gredia Anatasya Hutasoit (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Understanding God in Christian education plays a crucial role in the moral formation of children, as the theological concept of God forms the foundation for values, character, and ethical actions, developed from an early age. In Christian education, the process of moral formation does not simply rely on rules or customs, but rather rests on the child's personal relationship with God as a loving, guiding Being, and the source of truth. This study uses qualitative methods with a library research approach to explore how the concept of God according to Christian theology can serve as a foundation for the comprehensive moral formation of children. The aim of this study is to analyze how God's attributes such as love, holiness, justice, and faithfulness can be applied in the educational process so that the moral values formed are not formalistic but grow from a deep spiritual awareness. The research findings show that a proper understanding of God helps children recognize moral standards rooted in God's character, develop ethical attitudes, and strengthen the internal drive to live according to His will. This research is also expected to contribute to Christian educators in developing theological, contextual, and effective learning strategies to continuously cultivate children's morality in accordance with the principles of the Christian faith.